Primary Intracerebral Alveolar Soft Part Sarcoma: Report of a Case and Review of the Literature. (April 2022) - Caporalini, Chiara; Giordano, Flavio; Moscardi, Selene; Di Stefano, Gioia; Lenge, Matteo; Di Giacomo, Giampiero; Basile, Massimo; Zin, Angelica; Mura, Regina; Scagnet, Mirko; Alaggio, Rita; Sardi, Iacopo; et al.
Alveolar soft part sarcomas (ASPSs) are rare malignant tumors representing ∼1% of all soft tissue sarcomas. Most ASPS occurring in the central nervous system are metastases. In contrast, primary intracranial ASPSs are extremely rare and only 8 cases have been previously reported in English literature. Here, we report a case of primary alveolar soft part sarcoma in a 16-year-old female patient with no evidence of primary extracranial tumors. Histologically this case fulfilled the criteria of ASPS, and a molecular confirmation has been archived. To date, only 9 primary intracranial ASPS cases, including ours, have been reported in the literature. This report highlights the clinical and pathological characteristics, differential diagnosis, and molecular analysis of primary ASPS of the central nervous system.